DIGITAL LITERACY, INDUSTRY PRACTICES AND WORK READINESS FOR GENERATION Z - Panjaitan, Yehezkiel Ringgas; Purwana, Dedi; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to determine whether or not there is an influence of digital literacy, industrial work practices, and work readiness on generation Z in vocational high schools. This study uses a quantitative approach method. Respondents in this study were grade XI students at SMK Negeri 51 Jakarta with a population of 251 students. Sample selection using the Isaac & Michael table with an error rate of 5%, obtained a sample size of 146 students. The data obtained were then processed using SmartPLS 3.0 with Outer and Inner Models as data analysis techniques. The results of the calculation of Digital Literacy on Work Readiness show that the Original Sample score is 0.345 and the T-statistic is 6,570> 1.96 and the P-value is 0.000 <0.05; then for Industrial Work Practices on Work Readiness, the Original Sample score is 0.627 and the T-statistic is 12,141> 1.96 and the P-value is 0.000 <0.05. The results of the F-square calculation of Digital Literacy towards Job Readiness obtained a score of 0.193 and for Industrial Work Practices towards Job Readiness obtained an F-square score of 0.636.